Combined effects of solar radiation and airflow on endurance exercise capacity in the heat - Otani, H.; Kaya, M.; Tamaki, A.; Goto, H.; Tokizawa, K.; Maughan, R. J. (Physiology & Behavior, 2021)
This study investigated the combined effects of different levels of solar radiation and airflow on endurance exercise capacity and thermoregulatory responses during exercise-heat stress. Ten males cycled at 70% peak oxygen uptake until exhaustion in an environmental chamber (30°C, 50% relative humidity). Four combinations of solar radiation and airflow were tested (800 W/m2 and 10 km/h1 [High-Low], 800 W/m2 and 25 km/h [High-High], 0 W/m2 and 10 km/h [No-Low], and 0 W/m2 and 25 km/h [No-High]). Participants were exposed to solar radiation by a ceiling-mounted solar simulator (Metal halide lamps) and the headwind by two industrial fans. Time to exhaustion was shorter (p < 0.05) in High-Low (mean ± SD; 35 ± 7 min) than the other trials and in High-High (43 ± 6 min) and No-Low (46 ± 9 min) than No-High (61 ± 9 min). There was an interaction effect in total (dry + evaporative) heat exchange which was less in High-Low and High-High than No-Low and No-High, and in No-Low than No-High (all p < 0.001). Core temperature, heart rate and thermal sensation were higher in high (High-Low and High-High) than no (No-Low and No-High) solar radiation trials and in lower (High-Low and No-Low) than higher (High-High and No-High) airflow trials (p < 0.05). Mean skin temperature and rating of perceived exertion were higher in high than no solar radiation trials (p < 0.05). This study indicates that combining high solar radiation and lower airflow have negative effects on thermoregulatory and perceptual strain and endurance exercise capacity than when combining high solar radiation and higher airflow and combining no solar radiation and lower/higher airflow during exercise-heat stress.